Financialization, productive investment, and ecological sustainability through an Islamic economics lens in the G20 development - Muhammad Hisyam Syafii; Salmaa Dzakiyyah Az Zahrah; Husain Azhari; Rudyn Alaldaya (Indonesian Journal of Islamic Economics Research, 2026)
This study examines the structural relationship between financialization, productive investment, and ecological sustainability in G20 economies during 2020–2025, integrating structural macroeconometrics with the Islamic economic framework of maqashid al-shariah. Employing second-generation panel techniques  including CCEMG, AMG, SVAR, and panel threshold regression  the research identifies the structural consequences of riba-based financialization on productive investment efficiency and ecological sustainability outcomes. The findings reveal that financialization indicators  financial sector value-added, stock market capitalization, corporate debt, and financial profit share, identified as empirical manifestations of riba-driven financial expansion  exert significant negative long-run effects on total factor productivity growth, corroborating both the post-Keynesian crowding-out hypothesis and the Islamic economic proposition that riba structurally suppresses productive kasb by displacing investable surpluses from real capital formation. Conversely, all financialization indicators significantly increase carbon emission intensity and ecological footprint per capita, constituting empirical confirmation that riba-based financialization generates systematic darar violating hifz al-bi'ah. Threshold analysis identifies a wasatiyyah threshold of 94.7 percent of GDP beyond which negative impacts intensify nearly fourfold. The results collectively establish that excessive riba-based financial sector expansion violates maqashid al-shariah, underscoring the need for transition toward Islamic financial alternatives mudharabah, musharakah, green sukuk, and waqf-based instruments as empirically superior and normatively mandated responses to the financialization-sustainability crisis across G20 economies.